Combined Multiple Attenuation Methods and Geological Interpretation : Seram Sea Case Study 2D Marine Seismic Data - Tumpal Bernhard Nainggolan; Said Muhammad Rasidin; Imam Setiadi (Marine Geological Institute of Indonesia, 2019)
Multiple often and always appear in marine seismic data due to very high acoustic impedance contrasts. These events have undergone more than one reflection. This causes the signal to arrive back at the receiver at an erroneous time, which, in turn, causes false results and can result in data misinterpretation. Several types of multiple suppression have been studied in literature. Methods that attenuate multiples can be classified into three broad categories: deconvolution methods; filtering methods and wavefield prediction subtraction methods. The study area is situated on Seram Sea in between 131°15’E – 132°45’E and 3°0’S – 4°0’S, Seram Trough which is located beneath Seram Sea at northern part of the Banda-Arc – Australian collision zone and currently the site of contraction between Bird’s Head and Seram. This research uses predictive deconvolution and FK-filter to attenuate short period multiple from their move out, then continued by SRME method to predict multiple that cannot be attenuated from previous method, then followed by Radon transform to attenuate multiple that still left and cannot be attenuated by SRME method. The result of each method then compared to each other to see how well multiple attenuated. Predictive deconvolution and F-K filter could not give satisfactory result especially complex area where multiple in dipping event is not periodic, SRME method successfully attenuate multiple especially in near offset multiple without need subsurface information, while SRME method fails to attenuate long offset multiple, combination of SRME method and Radon transform can give satisfactory result with careful selection of the Radon transform parameters because it can obscure some primary reflectors. Based on geological interpretation, Seram Trough is built by dominant structural style of deposited fold and thrust belt. The deposited fold and thrust belt has a complexly fault geometry from western zone until eastern of seismic line.